The effect of hyperthermic preconditioning on the immune system in rat peritonitis - YEGEN, BERRAK (SPRINGER, 1999)
Objective: To assess whether hyperthermic (HT) preconditioning prevents the lethal effects of peritonitis by acting on the immune system. Design: Prospective, controlled, experimental study. Setting: Laboratory and animal facility of the university. Materials: Adult male Sprague Dawley rats. Interventions: In the HT groups animals were subjected to hyperthermia (42 degrees C, 15 min) and 8 h later peritonitis (P) (n = 14) was induced. In the normothermic (NT) groups, animals were subjected to normothermia (38 degrees C, 15 min) and 8 h later peritonitis (n = 14) was induced. Each group had a corresponding sham laparotomy group (n = 14). Six rats from each group were allowed to live 7 days for survival. In the control group (n = 4), rats were not anesthetized or heat treated. Measurements and results: Sixteen hours after peritonitis and laparotomy, rats were killed. Blood was taken to measure the percentage of CD4+, CD8+, CD4+CD56+, CD8+ CD11b+, NK+, B cells and the level of tumor necrosis factor. Grading of peritonitis and the measurement of free oxygen radicals in the peritoneal fluid were undertaken. All rats in the HT + P and sham laparotomy groups survived for 7 days, while in the NT + P group two rats died in 7 days. HT decreased the severity of peritonitis and increased the free oxygen radicals in the peritoneal fluid; however, the difference did not reach statistical significance. HT prevented the decrease in CD4+ and B cells and the increase in CD11b+. Conclusions: HT may have a protective role in sepsis by reducing the severity of peritonitis. A causal relation between hyperthermia and an improved immune system seems possible.
Keywords: heat shock proteins; preconditioning; hyperthermia; peritonitis; INFECTION; FEVER; BETA; CHEMILUMINESCENCE; PROTECTION; EXPRESSION; SURVIVAL; INJURY; MARKER; CELLS